1988
DOI: 10.1161/01.res.62.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and neural mechanisms of action of thyrotropin-releasing hormone in the rat.

Abstract: Tbe mechanisms mediating the etl'ects ofthyrotropin-releasing hormone (TRH) on the cardiovascular system were studied in the conscious rat. Intracerebroventricolar (i.c. v.) injection of TRH (8 pmol-80 nmollkg) induced dose-dependent lncreases in mean arterial pressure, heart rate, and cardiac index. Rindquarter blood Oow increased due to vasodilation, while an lncrease in renal and mesenteric vascular resistance caused a decrease in blood Oow in the respective organs. The plasma Ievels of norepinephrine a~d e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Grüfiths et al (24) reported an activation of the metabolic rate of brown adipose tissue of rats which was presumably mediated by a Stimulation of sympathetic nerve activity (5). Moreover, the Stimulation of LA by TRH as previously shown by Andrews and Sahgal (7) may constitute an indirect mode of metabolic activation due to an increased peripheral energy consumption.…”
Section: Central Ventila Tory Effeci's Of Thyrotropin-releasing Hormomentioning
confidence: 81%
See 1 more Smart Citation
“…Grüfiths et al (24) reported an activation of the metabolic rate of brown adipose tissue of rats which was presumably mediated by a Stimulation of sympathetic nerve activity (5). Moreover, the Stimulation of LA by TRH as previously shown by Andrews and Sahgal (7) may constitute an indirect mode of metabolic activation due to an increased peripheral energy consumption.…”
Section: Central Ventila Tory Effeci's Of Thyrotropin-releasing Hormomentioning
confidence: 81%
“…Moreover, high affinity TRH receptors have been localized in various CNS sites ( 4) suggesting that TRH may participate in the mediation or modulation of a variety of CNS functions under physiological conditions. This hypothesis is further validated by the profound effects of TRH on behavioral and autonomic functions after central and peripheral administration in experimental animals ( 5,6,7). In addition to its potent cardiovascular effects, including increases in arterial pressure and heart rate (5), TRH has been shown to increase ventilation in the anesthestized rat after intracerebroventricular (icv) application (6) or after microinjection into various brainstem structures (8).…”
Section: Introductionmentioning
confidence: 94%
“…A cable connecting the blood flow receptacle and the Doppler flowmeter (University of lowa, Bioengineering Facility, Model 545C-4) was attached to the animaland the mean blood flow continuously recorded on the physiograph. Vascular resistance was calculated by dividing the mean arterial pressure by blood velocity (Doppler shift in kilohertz) as earlier described (Haywood et a/.. 1981;Siren et al. 1988;Siren and Feuerstein, 1986).…”
Section: Measurement Oforgan Bloodjlowmentioning
confidence: 99%
“…TRH has been found to influence several important physiological functions including those of the autonomic nervous system (Feuerstein et al, 1983;Koskinen, 1986a;Seligsohn & Koskinen, 1991). Complex effects on the cardiovascular system have been demonstrated (Feuerstein et al, 1983;Siren et al, 1988). In the rabbit, TRH has been found to elicit cerebral vasodilatation by activation of an intrinsic cerebral vasodilating neural pathway (Koskinen, 1986a) which involves a yohimbinesensitive mechanism (Seligsohn & Koskinen, 1991).…”
Section: Introductionmentioning
confidence: 99%